Penerapan Model Pembelajaran Matematika PJBL dalam Meningkatkan Kreativitas dan Hasil Belajar Siswa Sekolah Dasar - Aisyah Putri Siregar; Melva Zainil (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The improvement of primary education quality has become a major focus in modern education. This study employs a literature review method to explore the application of the Project-Based Learning (PJBL) model in enhancing creativity and learning outcomes among elementary school students. The findings from various studies indicate that PJBL fosters critical and creative thinking, engages students actively, and promotes effective collaboration and communication. Furthermore, PJBL has proven to significantly improve learning outcomes by integrating real-world problem-solving with academic knowledge. This research concludes that PJBL is an effective, interactive, and innovative approach to create meaningful learning experiences. Recommendations include equipping teachers with proper training and resources to implement PJBL successfully in elementary.